LOCAL TIME FRACTIONAL REDUCED DIFFERENTIAL TRANSFORM METHOD FOR SOLVING LOCAL TIME FRACTIONAL TELEGRAPH EQUATIONS - Chu, Yu-Ming; Jneid, Maher; Chaouk, Abir; İnç, Mustafa; Rezazadeh, Hadi; Houwe, Alphonse (World Scientific Publ Co Pte Ltd, 2024)
In this paper, we seek to find solutions of the local time fractional Telegraph equation (LTFTE) by employing the local time fractional reduced differential transform method (LTFRDTM). This method produces a numerical approximate solution having the form of an infinite series that converges to a closed form solution in many cases. We apply LTFRDTM on four different LTFTEs to examine the efficiency of the proposed method. The yielded results established the effectiveness of LTFRDTM as a reliable and solid approach for obtaining solutions of LTFTEs. The solutions coincided with the exact solution in the ordinary case when mu = 1. It also required minimal amount of computational work and saved a lot of time.
Keywords: Yang's Local Fractional Derivative (LFD); LTFRDTM; Local Fractional Telegraph Equation; Approximate Solution